GENETIC VARIATION OF D7S1789 MICROSATELLITE LOCUS IN LONG-TAILED MACAQUES AT MOUNT PUSUK WEST LOMBOK - Meus, Febio Tomasini Marciano; Wandia, I Nengah; Suatha, I Ketut (Buletin Veteriner Udayana, 2019)
Long-tailed macaques ( Macaca fascicularis ) are Southeast Asian endemic animal with its behaviors and interactions form a protective cohesive group on its territory. Such patterns create distinctions that can be detected by microsatellite variations. This study revealed polymorphism of the D7S1789 microsatellite locus in a population of long-tailed macaques in Mount Pusuk West Lombok with the aim of knowing the genetic variation in the form of number of alleles, allele frequencies, heterozygosity and Hardy-Weinberg Equilibrium based on its allele’s distributing the Chi-square test. A total of 17 blood samples of long tailed macaque extracted used QIAamp DNA blood kit from QIAGEN to get DNA, DNA from locus D7S1789 microsatellite was replicated through 30 cycles of PCR technique, with annealing temperature 57°C. The alleles were raised by silver staining using 8% polyacrylamide gel. The results obtained two alleles with a frequency of 121 bp (0.794) and 130 bp (0.206), heterozygosity (0.337) and Hardy-Weinberg Equilibrium test (? 2 count) was 0.422 (? 2 table = 3.841; ? = 0.05; db = 1) which indicates a random mating population. It can be concluded that the D7S1789 microsatellite locus was polymorphic in the population of long-tailed monkeys in Mount Pusuk, West Lombok.